Princess in Training - Cabot, Meg (USA, 2005)
High school sophomore Princess Mia records in her diary her struggles with geometry, the expectation of being a college students' girlfriend, running for president of the student council, and a potential ecological disaster in her native land, Genovia...
Keywords: Diaries; High Schools; Interpersonal relations; Juvenile Fiction